Poverty and Charity in the Jewish Community of Medieval Egypt. - Cohen, Mark R.
1 online resource (284 pages)
Keywords: What was it like to be poor in the Middle Ages? In the past, the answer to this question came only from institutions and individuals who gave relief to the less fortunate. This book, by one of the top scholars in the field, is the first comprehensive book to study poverty in a premodern Jewish community--from the viewpoint of both the poor and those who provided for them. Mark Cohen mines the richest body of documents available on the matter: the papers of the Cairo Geniza. These documents, located in the Geniza, a hidden chamber for discarded papers situated in a medieval synagogue in Old Cairo, were preserved largely unharmed for more than nine centuries due to an ancient custom in Judaism that prohibited the destruction of pages of sacred writing. Based on these papers, the book provides abundant testimony about how one large and important medieval Jewish community dealt with the constant presence of poverty in its midst. Building on S. D. Goitein's Mediterranean Society and inspired also by research on poverty and charity in medieval and early modern Europe, it provides a clear window onto the daily lives of the poor. It also illuminates private charity, a subject that has long been elusive to the medieval historian. In addition, Cohen's work functions as a detailed case study of an important phenomenon in human history. Cohen concludes that the relatively narrow gap between the poor and rich, and the precariousness of wealth in general, combined to make charity “one of the major agglutinates of Jewish associational life“ during the medieval period.